KARAKTERISTIK SIFAT KIMIA DAN KONDISI MIKROBA TANAH PADA LAHAN PERKEBUNAN NANAS (Ananas comosus) DENGAN TINGKAT PRODUKSI YANG BERBEDA - Sunaryo, Kusuma Handayani (Jurnal Agroekoteknologi, 2017)
Pineapple cultivation activities that have been carried out over the years result in diminished soil fertility quality. This can be caused by the use of fertilizers and pesticides used in each pineapple cultivation cycle. Soil microbial activity, microbial biomass, organic C, and soil nutrient conditions are indicators of soil hygiene by the biochemical processes associated with nutrient cycles, especially nitrogen and organic matter content. The purpose of this research was to know how the characteristics of soil chemical properties and total microbial on land that has received fertilizer treatment during planting process. The location of the soil sampling was based on the difference of production level ie 9 blocks of land location consisting of 6 blocks of low production site location and 3 blocks of high production land. Each block of production site land, soil samples were collected by 9 soil samples and composite into one sample. Research data was analyzed by T test and correlation. From the results of the research on the land with different production results, it was found that only the P and N content of elements with significant value <0.05 of the rest was no significant value, although it was not mean that microb and other soil chemical properties have no role to plant growth. Because in every process of growth was influenced by many supporting factors.Keywords: Chemical characteristics, Soil microbes, Nutrient element